Le Bassin minier du Nord-Pas-de-Calais, un patrimoine évolutif et vivant. Entre conservation et évolution, enjeux et nouveau paradigme pour les projets d’architecture - Philippe Prost; Lucas Monsaingeon (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The Nord-Pas-de-Calais mining basin in France is characterized by landscapes, urban-planning and architecture that is the result of two centuries of intensive coal exploitation. The region is currently in brutal transition, after the closure of the mines from 1960 to 1990. Inscribed on the World Heritage Site list as an "evolving and living cultural landscape" in 2012, the recognition of this territory, considered a force of resilience for an ambitious transition, has raised the question of preservation and architecture - with more than 28,000 registered housings - on land rarely approached and on an unprecedented scale, raising many questions for architects and preservationists. We will first look at the challenges of this heritage recognition for existing architectural projects, then we will present the context and method of practice-led research commissioned by the Mining Basin Mission and conducted by the Atelier d’Architecture Philippe Prost between 2017 and 2019. Lastly, we will detail the operational results of this work intended to lay the foundations for a shared reference system to intervene on the mining heritage, between preservation and evolution.